2019
DOI: 10.30534/ijatcse/2019/95862019
|View full text |Cite
|
Sign up to set email alerts
|

An Optimized Newton-Raphson Algorithm for Approximating Internal Rate of Return

Abstract: The internal rate of return (IRR) is the most widely-used method in measuring the rate of return on investment (RROI), which helps investors decide whether an investment is viable or not. Iterative root-finding algorithms are the most efficient technique in calculating IRR, amongst which, the Newton-Raphson algorithm is the most popular and the fastest algorithm. However, when the primary unknown, which is provided by the user, is far from the actual root, the result of the algorithm, oftentimes, does not conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The Newton-Raphson algorithm is practical algorithm because of its quick convergence yet given a certain accuracy level (Nagares et al, 2019;Ypma, 1995). This method is very conventional for its fast rate convergence and improving the convergence quality.…”
Section: Newton-raphson Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Newton-Raphson algorithm is practical algorithm because of its quick convergence yet given a certain accuracy level (Nagares et al, 2019;Ypma, 1995). This method is very conventional for its fast rate convergence and improving the convergence quality.…”
Section: Newton-raphson Methodsmentioning
confidence: 99%
“…However, this study aims to focus on solving the interest rate of study loan based on Newton-Raphson method. This method is selected due to its properties that requires fewer iterations to achieve convergence and this method is found much faster, more reliable, and produces accurate results (Nagares et al, 2019). In this study, a mathematical model of ordinary annuity to find interest rate of study loan is shown in Equation ( 1).…”
Section: Methodsmentioning
confidence: 99%
“…The convergence analysis of these algorithms with different was studied by several academics. (see Zoutendijk [10], Powell [11,12], Z. Wei [13], Zhi-Feng Dai [14], Al-Baali [15], Dai and Yuan [16], Narene et al, [29]).…”
Section: Introductionmentioning
confidence: 99%